Association Between Infantile Spasms and Nonaccidental Head Injury. (May 2014) - Birca, Ala; D'Anjou, Guy; Carmant, Lionel
Infantile spasms constitute a severe epileptic encephalopathy of infancy with poor long-term developmental outcome. Many diverse etiologies have been associated with infantile spasms, but the pathophysiological process is still not fully understood. We describe 2 cases of previously healthy 1- and 3-month-old infants who suffered a nonaccidental head injury with extensive cerebral lesions. Both presented with acute focal seizures rapidly controlled with phenobarbital. Nevertheless, they developed infantile spasms after a latency period of 3-4 months. Spasms were rapidly controlled with vigabatrin. Both children manifested with developmental delay, either exacerbated (case 1) or elicited (case 2) by infantile spasms. Our report highlights nonaccidental head injury as a risk factor for developing infantile spasms following a seizure-free latency period. A better understanding of the pathophysiology linking accidental brain trauma with infantile spasms could lead to more effective neuroprotective strategies. In the meantime, increased awareness and follow-up are warranted.